1998
DOI: 10.1002/(sici)1097-4547(19981201)54:5<584::aid-jnr3>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor isoforms are sequentially expressed in oligodendrocyte lineage cells during rat cerebral development

Abstract: In the mammalian brain, thyroid hormones regulate myelination. Their actions are mediated by interactions with nuclear receptors that function as ligand-regulated transcription factors. Two genes, alpha and beta, encode different isoforms, of which only the beta and alpha1 isoforms are authentic nuclear triiodothyronine (T3)-receptors (NT3R). In agreement with the important role of T3 on myelination and oligodendrocyte generation, the presence of NT3Rs has been reported in oligodendrocytes and their precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…There appears to be general consensus that both OPCs and OLGs express TRα and that OLGs express TRβ (Carré et al, ; Fierro‐Renoy, 1995), in agreement with Bury et al (), who showed that TRα and TRβ colocalize in OLGs before CNPase is expressed. Very recently, Baxi et al () showed that a TRβ agonist promotes oligodendrogenesis in rodents and in human OPCs in vitro .…”
Section: Discussionsupporting
confidence: 63%
“…There appears to be general consensus that both OPCs and OLGs express TRα and that OLGs express TRβ (Carré et al, ; Fierro‐Renoy, 1995), in agreement with Bury et al (), who showed that TRα and TRβ colocalize in OLGs before CNPase is expressed. Very recently, Baxi et al () showed that a TRβ agonist promotes oligodendrogenesis in rodents and in human OPCs in vitro .…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, thyroid hormones, acting through thyroid hormone receptors (TRs) and play an important role in amphibian metamorphosis and vertebrate development (Nagasawa et al, 1997). These receptors are expressed in neurons, oligodendrocytes, and astrocytes, the predominant cell types in the brain (Mellström et al, 1991; Strait et al, 1991, 1997; Bradley et al, 1992; Carlson et al, 1994; Carre et al, 1998). Taking into account that thyroid hormone exerts specific effects on brain development by regulating gene expression (Oppenheimer and Schwartz, 1997; Zhang and Lazar, 2000), some studies demonstrate that several genes are regulated directly by thyroid hormones at the transcriptional level and at an earlier stage of cerebellar development, i.e., during embryonic day 18–postnatal day 0 (Alvarez‐Dolado et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although developing rat OPCs seem not to express the TR β gene (Baas et al ., 1994a,b; Carre et al ., 1998), we previously showed that overexpression of TRβ1 in these cells accelerated their differentiation in the presence of PDGF and TH (Billon et al ., 2001). These findings are consistent with our present results, as TRβ1 and TRα1 can bind to the same TREs and recruit some of the same co‐regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%